Induction of resistance in tomato against buckeye rot (Phytophthora nicotianae var. parasitica) - Sharma, Adikshita; Shridhar, B.; Sharma, Amit; Sharma, Monica (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2021)
Buckeye rot disease of tomato caused by Phytophthora nicotianae var. parasitica is the most destructive disease for reducing tomato yields especially in those regions where fruiting coincides with rainy season. In the present study, the pathogen was characterized by sequencing the DNA region coding for internal transcribed spacer (ITS) region and sequence was deposited in NCBI with accession no. MF398189. The phylogenetic analysis using the Maximum Composite Likelihood (MCL) approach revealed that the isolated pathogen clustered together with P. nicotianae with high bootstrap value of 99%. Incubation period of 120 h was observed in pin-prick method of pathogen inoculation compared to 168 h in surface inoculation method. Further, the disease resistance induced by nine different elicitors of induced resistance against buckeye rot disease of tomato were studied under field conditions for two consecutive years 2016 and 2017. Minimum disease incidence of 9.57% and 7.93% was observed with foliar spray of ß-aminobutyric acid (2 mM) for 2016 and 2017, respectively. It was followed by potassium chloride (100 mM) with disease incidence of 11.32% and 8.85% for year 2016 and 2017, respectively. Maximum fruit yield of 7.02 kg and 8.12 kg was found in treatment with ß-aminobutyric acid as compared to 2.61 kg and 2.55 kg in control for year 2016 and 2017, respectively.